Solar cell, electrode structure, battery module, power generation system and manufacturing method

JP3250186UActive Publication Date: 2025-02-17ZHEJIANG AIKO SOLAR ENERGY TECH CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024600137U
Authority / Receiving Office
JP · JP
Patent Type
Utility models
Current Assignee / Owner
Priority Date
2022-03-11
Filing Date
2023-03-13
Publication Date
2025-02-17
Estimated Expiration
2033-03-13

AI Technical Summary

Benefits of technology

【0077】 下記表hに示すように、本開示の有益な効果をよりよく理解しやすくするために、まずモデリング計算により本開示による太陽電池の性能向上を評価する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0003250186000001_ABST
    Figure 0003250186000001_ABST
Patent Text Reader

Abstract

The present disclosure discloses an electrode structure of a solar cell, belonging to the technical field of photovoltaic cells, the electrode structure includes a conductive layer, and a seed layer is provided at one end of the conductive layer connected to the solar cell, and by ensuring that the width of the seed layer is smaller than the width of the conductive layer and that the width of the conductive layer is larger than the width of the seed layer, low line resistance is achieved, the risk of the conductive layer diffusing into the solar cell is avoided, and the photoelectric conversion efficiency of the cell itself is ensured. The present disclosure further discloses a solar cell, a battery module, and a power generation system to which the electrode structure is applied.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This invention claims priority to a patent application filed on March 11, 2022, bearing application number 202210239656.3 and entitled "Solar Cell, Electrode Structure, Battery Module, Power Generation System and Manufacturing Method," the entire contents of which are incorporated by reference into this disclosure.

[0002] The present disclosure relates to the technical field of photovoltaic cells, and in particular to solar cells, electrode structures, battery modules, power generation systems and manufacturing methods. [Background technology]

[0003] A solar cell is a photoelectric semiconductor sheet that generates electricity directly from sunlight. It is also called a "solar chip" or "photocell". When it is exposed to light that meets certain illuminance conditions, it can instantly output a voltage and generate an electric current when a circuit is present. Physically, it is called photovoltaic power generation (abbreviated as PV), which is also abbreviated as photovoltaic power.

[0004] As shown in FIG. 1, the structure of a solar cell currently available on the market includes a base 1000 on which a conductive film layer 1001 is provided. However, this structure allows the material molecules in the conductive film layer 1001 to easily diffuse into the base 1000, causing the formation of complex pairs, resulting in reduced photovoltaic efficiency. Summary of the Invention [Problem to be solved by the invention]

[0005] The present disclosure aims to provide an electrode structure for a solar cell in order to solve the problems in the background art described above. [Means for solving the problem]

[0006] In order to achieve the above object, the present disclosure provides the following technical means.

[0007] The electrode structure of a solar cell includes a conductive layer, a seed layer is provided at one end of the conductive layer connected to the solar cell, the width of the seed layer is smaller than the width of the conductive layer, a predetermined surface of the conductive layer and a surface of the solar cell form a suspension structure, and the predetermined surface is a surface of the conductive layer that is adjacent to the seed layer and is not covered by the seed layer.

[0008] Compared with the prior art, the present technical solution has the following advantages:

[0009] 1) By ensuring that the width of the conductive layer is larger than that of the seed layer, low line resistance is achieved, and the risk of the conductive layer diffusing into the solar cell is avoided, thereby ensuring the photoelectric conversion efficiency of the cell itself.

[0010] 2) The "suspension structure" forms a multiple reflection structure to improve the light reflection effect, increase the short-circuit current, and improve the battery conversion efficiency.

[0011] In one exemplary embodiment, the seed layer is made of an alloy material, the components of the seed layer include a functional component and a strengthening component, and the functional component and the strengthening component are mixed in a certain ratio.

[0012] In one exemplary embodiment, the functional component is a metal having a wavelength range of 850 nm to 1200 nm and an average refractive index of less than 2.

[0013] In one exemplary embodiment, the functional component is one or more of Al, Ag, Cu, Mg, and the reinforcing component includes one or more of Mo, Ni, Ti, W, Cr, Si, Mn, Pd, Bi, Nb, Ta, Pa, V, the content percentage of the functional component is >50%, the content percentage of the functional component is the ratio between the content of the functional component and the total content, and the total content is the sum of the content of the functional component and the content of the reinforcing component.

[0014] In an exemplary embodiment, the seed layer is fabricated by one of the following methods: physical vapor deposition, screen printing, chemical vapor deposition, electroplating, or chemical plating.

[0015] In one exemplary embodiment, the conductive layer is made of a conductive metal, and the material of the conductive layer includes one or more of Cu, Ag, and Al.

[0016] In an exemplary embodiment, the conductive layer is fabricated by one of the following methods: physical vapor deposition, screen printing, chemical vapor deposition, electroplating, or chemical plating.

[0017] In one exemplary embodiment, the electrode structure further includes a protective layer provided on a surface of the conductive layer remote from the seed layer, the protective layer being made of Sn or Ag, and the protective layer being manufactured by one of the following methods: physical vapor deposition, screen printing, chemical vapor deposition, electroplating, or chemical plating.

[0018] In an exemplary embodiment, the suspension structure has a suspension mean height range of 10 nm to 50 μm, and the suspension mean height is the distance between the predetermined surface and the surface of the solar cell.

[0019] In one exemplary embodiment, a layer of dielectric film is further provided on the surface of the solar cell, an opening is formed in the dielectric film to expose a portion of the surface of the solar cell, and the seed layer locally contacts the solar cell through the opening.

[0020] In one exemplary embodiment, a transparent conductive oxide thin film is further provided between the seed layer and the dielectric film, and a portion of the transparent conductive oxide thin film contacts the solar cell through the opening provided in the dielectric film.

[0021] In an exemplary embodiment, the width of the seed layer=(20%-98%)*the width of the conductive layer.

[0022] In one exemplary embodiment, the width of the conductive layer minus the width of the seed layer > 5 μm.

[0023] In an exemplary embodiment, the width of the seed layer=(30%-90%)*the width of the conductive layer.

[0024] In one exemplary embodiment, the width of the conductive layer minus the width of the seed layer > 10 μm.

[0025] In one exemplary embodiment, the seed layer is comprised of a plurality of stacked sub-seed layers.

[0026] In one exemplary embodiment, the content of the functional component in the stacked subseed layers gradually decreases along a direction away from the solar cell.

[0027] In an exemplary embodiment, the seed layer has a thickness of 10 nm to 1000 nm.

[0028] In an exemplary embodiment, the conductive layer has a thickness of 1 to 800 μm.

[0029] The present disclosure further discloses a solar cell, a solar cell module, and a solar power generation system, all of which are based on the electrode structure described in any of the above technical means.

[0030] At the same time, the present disclosure further discloses a manufacturing method for manufacturing the electrode structure, specifically, forming a patterned mask layer over the solar cell; forming a pre-seed layer on a surface of the solar cell adjacent to the mask layer; forming a conductive layer on a surface of the pre-seed layer remote from the solar cell; using the mask layer as a mask to remove the preliminary seed layer not in contact with a substrate to obtain a seed layer, and then removing the patterned mask layer. [Brief description of the drawings]

[0031] [Figure 1] FIG. 1 is a schematic diagram of an overall configuration of a conventional technology. [Diagram 2] 1 is a schematic diagram illustrating an overall configuration of an electrode structure according to the present disclosure. [Diagram 3] FIG. 13 is a modeling comparison of the light reflectance of seed layers of different materials according to the present disclosure. [Figure 4] FIG. 1 is a comparison diagram of the diffusion coefficients of Cu and other metals. [Diagram 5] FIG. 1 is a schematic diagram of an electrode detachment failure. [Figure 6] 1 is a schematic diagram of a connection structure between a main grid and a fine grid of a solar cell. [Figure 7] FIG. 1 is a schematic diagram of a conventional method for electroplating an electrode. [Figure 8] FIG. 1 is a schematic diagram of a method for electroplating an electrode according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] Hereinafter, the technical means in the embodiments of the present disclosure will be clearly and completely described with reference to the drawings in the embodiments of the present disclosure, and obviously, the described embodiments are only some embodiments of the present disclosure, but not all of them. EXAMPLES

[0033] For the solar cell as shown in FIG. 2, in this embodiment, the solar cell is a back-contact type solar cell, and the back-contact type solar cell includes a substrate 5, on which an electrode structure is provided.

[0034] The electrode structure includes a conductive layer 1, and a seed layer 2 is provided at one end of the conductive layer 1 connected to the substrate 5, the width of the seed layer 2 is smaller than the width of the conductive layer 1, and a predetermined surface of the conductive layer and the surface of the solar cell form a suspension structure, and the predetermined surface is a surface of the conductive layer close to the seed layer and not covered by the seed layer, that is, the part of the conductive layer 1 beyond the seed layer 2 and the substrate surface form a suspension structure. First, by ensuring that the width of the conductive layer 1 is larger than the width of the seed layer 2, low line resistance is realized, and the risk of molecules in the conductive layer 1 diffusing to the substrate 5 is avoided, and the photoelectric conversion efficiency of the cell itself is guaranteed. Second, the "suspension structure" is provided. Combining this embodiment, specifically, the end face of the conductive layer 1 facing the substrate 5 is provided on the substrate 5 with a gap therebetween, and the width of the entire conductive layer 1 is larger than the width of the entire seed layer 2, so that an air layer is formed, which improves the light reflection effect, improves the short-circuit current of the solar cell, and improves the conversion efficiency of the cell.

[0035] The suspension average height of the air layer ranges from 10 nm to 50 μm, and the suspension average height is the distance between the specified surface and the surface of the solar cell. As can be seen from FIG. 3, the correlation between the light reflection condition and the suspension average height is such that as the thickness of the air layer gradually increases, the light reflection condition becomes better and remains stable.

[0036] In this embodiment, the conductive layer 1 is made of a conductive metal, the material of which includes one or more of Cu, Ag, and Al, and the conductive layer 1 is manufactured by one of physical vapor deposition, screen printing, chemical vapor deposition, electroplating, or chemical plating, and is preferably manufactured by physical vapor deposition.

[0037] The seed layer 2 is made of an alloy material, and its components include a functional component 20 and a reinforcing component 21. The functional component 20 and the reinforcing component 21 are mixed in a certain ratio. The functional component 20 is a metal material having an average refractive index of less than 2 in the wavelength range of 750 nm to 1250 nm. The functional component 20 reduces back reflection (back reflection). The functional component 20 enhances the effect of the antireflection effect, and the reinforcing component 21 improves the binding effect between the conductive layer 1 and the substrate 5. In this embodiment, the functional component 20 is one or more of Al, Ag, Cu, and Mg, and the reinforcing component 21 includes any one or more of Mo, Ni, Ti, W, Cr, Mn, Pd, Bi, Nb, Ta, Pa, Si, and V, and depending on the content ratio, the functional component>50%, i.e., the content ratio of the functional component>50%, the content ratio of the functional component is the ratio between the content of the functional component and the total content, and the total content is the sum of the content of the functional component and the content of the reinforcing component.

[0038] Moreover, the seed layer is manufactured by one of the following methods: physical vapor deposition, screen printing, chemical vapor deposition, electroplating or chemical plating, and preferably physical vapor deposition.

[0039] The electrode structure further includes a protective layer 6 provided on a surface of the conductive layer 1 remote from the seed layer, the protective layer 6 being made of one of Sn or Ag, and the protective layer 6 being manufactured by one of physical vapor deposition, screen printing, chemical vapor deposition, electroplating or chemical plating, in this embodiment, the protective layer 6 is manufactured by electroplating or chemical plating using Sn as the selective material, the function of which is to protect the conductive layer 1 with the Sn layer to avoid oxidation and to improve the connection strength with the solder strip in the case of subsequent assembly of a battery cell module.

[0040] To further explain the electrode structure, it will be described together with its manufacturing process, which includes the following steps 1) to 4).

[0041] In step 1), a patterned mask layer is formed on a substrate 5 (not shown in the figure because the mask layer is removed in later processing), and the hard mask plate is manufactured by one of two methods: hard mask plate and laser etching. For a description of the hard mask plate, please refer to the description of the Chinese patent with application number 2021116201937.

[0042] In step 2), a seed layer 2 is formed based on step 1), the thickness of the seed layer 2 is 10 nm to 1000 nm, and the seed layer 2 may have a single layer structure or is formed by stacking multiple sub-seed layers, and when multiple sub-seed layers are stacked, the content of functional component 20 in the sub-seed layers stacked in the direction away from the substrate 5 gradually decreases.

[0043] Specifically, when a multi-layer structure is selected and used, the method of gradually changing the content of the functional component 20 is used, mainly because the functional component 20 can enhance the light reflection effect, but no improvement is observed in strengthening the connection strength when the conductive layer 1 is provided on the substrate 5; as the content of the functional component 20 gradually decreases, the reinforcing component 21 gradually increases, but overall the content ratio of the functional component 20 is controlled to be >50%, thereby strengthening the connection strength when the conductive layer 1 is provided on the substrate 5.

[0044] In step 3), a conductive layer 1 is formed on a surface of the seed layer 2 that is remote from the solar cell, the conductive layer having a thickness of 1 to 800 μm and produced by physical vapor deposition; In step 4), the seed layer 2 and the patterned mask layer that are not covered by the conductive layer 1 are removed.

[0045] In this embodiment, the width of the seed layer 2 is 10% to 90% of the width of the conductive layer 1, and the width of the conductive layer 1-the width of the seed layer 2>10 μm. In another embodiment, the width of the seed layer 2=(30% to 90%)*the width of the conductive layer 1, and the width of the conductive layer 1-the width of the seed layer 2>10 μm.

[0046] At present, Ag paste is used as the electrode material in mass-produced crystalline silicon solar cells, and the cost of Ag paste accounts for about 30% of the non-silicon cost of the cell. Manufacturing techniques that reduce the amount of Ag used or do not use Ag can effectively reduce the manufacturing cost of solar cells. Cu is a good substitute for Ag, and its advantages as a conductive material compared to Ag are shown in Table A below.

[0047] [Table 1]

[0048] As can be seen from Table a above, Cu has excellent properties such as relatively stable chemical properties, excellent ductility, sufficiently low volume resistivity, and being available in large quantities and inexpensive (nearly 1 / 72 of the price of Ag material), making it an effective substitute for Ag. However, the application of Cu to solar cells is limited by two important properties. The first is that the diffusion coefficient of Cu is too large. Figure 4 is a schematic diagram of the diffusion coefficients of common metals, where the horizontal and vertical axes in Figure 4 represent the inverse of temperature (unit: Kelvin K) and the diffusion coefficient of metal elements, respectively. As can be seen from Figure 4, the diffusion coefficient of Cu is much higher than other metals, and is >5 orders of magnitude higher than Ag / Al, etc.

[0049] Second, Cu defects have a large capture cross section for holes, which significantly reduces the minority carrier lifetime and further reduces the electrical performance of the solar cell. The effects of Cu content on minority carrier lifetime and cell performance are shown in Table b below.

[0050] [Table 2]

[0051] As can be seen from Table b above, with increasing Cu content, the minority carrier lifetime and cell efficiency decrease significantly. 3 Even so, the battery efficiency drops by 0.29%.

[0052] In conventional technology, Ni (nickel) is usually used as a barrier layer for Cu diffusion and can bond well with the substrate and Cu electrode. The general flow of the implementation plan is to prepare a substrate after electroplating, open the film with a laser, electroplate Ni, and electroplate a Cu layer. However, in the course of research, it was discovered that when Ni is used as a barrier layer for Cu, it has a major defect in that its reflective effect in the long wavelength range is low, which reduces the light trapping effect of the cell and further reduces the conversion efficiency of the cell.

[0053] Comparative data on the optical performance of cells with Ni+Cu and Ag electrode materials is shown in Table c below.

[0054] [Table 3]

[0055] As can be seen from Table c above, the combination of Ni+Cu significantly reduces the short circuit current of the battery, and the simulation results show that the short circuit current density is 0.75mA / cm 2 The experimental results showed that the short circuit current density was 1.36 mA / cm 2 The decrease was greater than theoretically predicted.

[0056] The light trapping effect of common metals is analyzed below.

[0057] Currently, the thickness of a finished silicon wafer for a battery is about 150um, and light with a wavelength of >850nm can effectively penetrate this thickness. Generally, the band gap of Si is 1.12eV, and light with a wavelength of >1200nm is difficult to excite electron-hole pairs, so when considering the light trapping effect, the focus is mainly on the wavelength range of 850-1200nm. Table d below shows the interface reflectance of different metals and the market price as of February 2022.

[0058] [Table 4]

[0059] As can be seen from Table d above, the difference in interface reflectance between different metals is large, and the four metals Ag / Al / Cu / Mg can obtain relatively ideal short circuit current results, and when used in the seed layer 2, they can all achieve effective light trapping effect. Further analysis shows that one important role of the seed layer 2 is to barrier Cu, so Cu is not used as the seed layer 2. Mg is not a good choice because its chemical properties are too active, and Ag is not a good choice because of its high price, while Al is the ideal metal for the seed layer 2, with excellent back reflectance effect, relatively stable chemical properties, and low cost, only 1 / 223 of Ag and 1 / 3 of Cu.

[0060] However, pure Al metal is used as the seed layer 2, and the bonding between Al and other metals is weak. The technology of using pure Al as the seed layer 2 may result in the reliability of the product not meeting the standards. In the product, when the product is heated or cooled or bent, or due to stress at the welded part caused by module welding, the Al and the outer layer metal may separate and fall off, resulting in another problem of failure.

[0061] Due to the weak bonding strength between Al and Cu, it is easy to cause the falling off of the vast grid lines. To solve this problem, various improvement methods have been tried, such as increasing the contact area of ​​Al / substrate, promoting the diffusion between metals by raising the temperature of the sample, and adding new materials such as TiW between the Al / Cu materials, but the effects are not ideal. Finally, it was found that by directly adding a strengthening component to the Al material, which can form a good interconnection with Cu as the seed layer 2, no extra annealing treatment is required after Cu electroplating, that is, it can form a good cross-connection of the seed layer 2 / conductive layer 1, and greatly improve the adhesion of the conductive layer 1, thus finally solving this problem.

[0062] Further verification has revealed that reinforcing components 21 such as Mo, Ni, Ti, W, Cr, Mn, Pd, Bi, Nb, Ta, Pa, Si, and V have a clear adhesive strength improving effect.

[0063] Furthermore, as can be seen from Table d, the materials Mo, Ni, Ti, W, Cr, Mn, Pd, Bi, Nb, Ta, Pa, Si, and V have a relatively low reflectivity, and adding too much of them leads to a decrease in optical performance. Taking W as an example, if we simply assume that the performance of the alloy components is the average enhancement value of the components, we obtain the estimated results shown in Table e below.

[0064] [Table 5]

[0065] When the W content is 30%, the current loss is 0.36 mA / cm 2 Although the battery conversion efficiency decreases by about 0.2% and the current loss is relatively large, taking into consideration the cost reduction and the solution of the reliability problem by using Cu instead of Ag, it is worth accepting. Therefore, a reinforcing component of ≦30% is considered to be the recommended value.

[0066] Furthermore, the proportion of the reinforcing component 21 in the seed layer 2 can be distributed unevenly, and thus better performance effects can be obtained. The principle is that by reducing the content of the reinforcing component 21 in the part close to the substrate 5, the light reflection can be enhanced, and by relatively increasing the content of the reinforcing component in the part in contact with the metal of the conductive layer 1, the bonding strength with the metal of the conductive layer can be improved.

[0067] Table f below is a comparison of the weld pull forces for different electrode technologies.

[0068] [Table 6]

[0069] As can be seen from Table f above, the grid lines in the seed layer 2 made of pure Al have low tensile strength, which is much lower than that of ordinary Ag electrodes, and although the welding tensile strength is improved after direct insertion of TiW material into Al and Cu, it is still insufficient, and in this disclosure, the solar cells manufactured using the Al alloy seed layer 2 have higher welding tensile strength than that of ordinary Ag electrodes.

[0070] By using Al as the main component, the adhesion between the seed layer and the Cu conductive layer and the light trapping effect of the solar cell are improved, and Table g shows data on the technical effects of combining each single reinforcing component with Al, which is the main component.

[0071] [Table 7]

[0072] As can be seen from the above experimental data, Cr, Mn, Pd, Bi, Nb, Ta, Pa, Si, and V can also be used as reinforcing components to improve the adhesion between the seed layer and the Cu conductive layer and the light trapping effect of the solar cell. It should be emphasized that there are hundreds of combinations of one or more of the reinforcing components Mo, Ni, Ti, W, Cr, Mn, Pd, Bi, Nb, Ta, Pa, Si, and V with Al, and it is impossible to provide experimental comparison data for all compositions. Therefore, in a specific embodiment, on the premise of providing experimental data using Ni, Mo, Ti, W, Cr, Mn, Pd, Bi, Nb, Ta, Pa, Si, and V as the sole reinforcing component, it is clear and obvious that the combination of other reinforcing components with the main component Al can also achieve the desired technical effect.

[0073] Furthermore, the thickness of the seed layer 2 is preferably ≧30 nm. As can be seen from experiments, a seed layer 2 with a thickness of 30 nm is sufficient to provide a barrier to the diffusion of Cu metal. The reason why the thickness is ≦300 nm is because cost control is the main consideration. For example, when the seed layer 2 is manufactured by physical vapor deposition, even though Al is cheaper than other metals, the cost impact of the Al target is still not negligible. The thicker the seed layer 2, the lower the production capacity of the equipment, which is unfavorable for the popularization of large-scale manufacturing. Therefore, the thickness of the seed layer is preferably between 30 and 300 nm.

[0074] Furthermore, in order to save the cost of alloy target and further limit the diffusion of Cu metal into the substrate, a layer of transparent conductive oxide thin film 3 can be added between the alloy seed layer 2 and the substrate 5, so that the long wavelength light can be transmitted through the transparent conductive oxide thin film 3 and effectively reflected at the interface of the seed layer 2, also achieving ideal performance and reliability results.

[0075] Moreover, a single dielectric film 4 is further provided on the surface of the substrate 5 , an opening 40 is formed in the dielectric film 4 , and the seed layer 2 is locally in contact with the substrate 5 through the opening 40 .

[0076] The seed layer 2 is in conductive contact with the substrate 5 through the openings 40, thereby resolving the contradiction between the electrode width and the opening damage, and greatly increasing the electrode width, reducing the line resistance of the solar cell while solving the problem that the grid lines are easily dropped off due to the narrow line width when the electrodes are electroplated for a long period of time. In addition, the independently developed horizontal electroplating equipment is used to perform slim electroplating on the solar cell to be electroplated after the growth of the seed layer 2 is completed, thereby solving the problem that the electroplating efficiency of the vertical electroplating method in the prior art is low and cannot be applied to large-scale electroplating.

[0077] To better understand the beneficial effects of the present disclosure, modeling calculations are first used to evaluate the performance improvement of solar cells according to the present disclosure, as shown in Table h below.

[0078] [Table 8]

[0079] As can be seen from Table h above, in the conventional solution, as the electrode width increases, the electrode resistance loss gradually decreases, but the efficiency loss due to front shading and efficiency loss due to combination gradually increase, which is a contradiction. The final conclusion is that the smaller the electrode width, the smaller the loss. However, even when reduced to 30 μm, the efficiency loss is already 1.3%. At the same time, at this width, the adhesion strength of the grid line is insufficient, which leads to serious reliability problems. This is the main reason why electroplating technology has not been applicable to large-scale mass production in the past.

[0080] The present disclosure resolves the contradictions in the prior art: 1) by using a back-contact cell structure, there is no electrode on the front side, solving the light-shielding loss of the electrode; 2) by using PVD to realize the seed layer 2, the electrode width can be made larger than the opening size, which greatly reduces laser damage and obtains an ideal electrode width; and 3) the electrode is wide enough (preferably, width > 30um, more preferably, the width range is 80-400um), which can greatly increase the adhesion between the electrode and the seed layer 2, and between the seed layer 2 and the substrate 5.

[0081] The influence of the electrode width on the adhesive strength and reliability will be emphasized below.

[0082] As shown in Figure 5, three main mechanisms of electrode detachment failure are illustrated.

[0083] 1) Failure type 1 is transverse shear stress. In Figure 6, N1 indicates the external force, and N2 indicates the adhesive force. The larger the electrode width, the smaller the difference between the moment arms of N2 and N1, which can reduce the risk of this type of failure.

[0084] 2) Failure type 2 is vertical tensile force. The larger the electrode width, the larger the adhesion area and the greater the adhesion force, which can reduce the risk of this type of failure. 3) Failure type 3 is the corrosion of the electrodes caused by water vapor, which is a decomposition product of the module packaging material. Ni, Mo, Ti, etc. are more active than Cu, and especially the acidic decomposition products will gradually corrode the seed layer during long-term aging. Therefore, if the electrode width is too narrow, it will affect the long-term aging performance of the product.

[0085] Another factor that limits the large-scale mass production of traditional electroplating technology is the low production capacity, poor uniformity, and poor appearance / performance of the electrode clamping area, which will be explained below.

[0086] In the prior art, it is necessary to open a film under the electrode with a laser to expose the area that needs to be electroplated, and then connect a cathode to the open film area to form the cathode of the electroplating system on the substrate, which brings about the following problems:

[0087] As shown in FIG. 6, the four wide electrodes 300 that span the entire battery vertically are called main grids, and the thin electrodes 400 between the main grids are called fine grids. The main grids need to be large in width because they collect the current collected by the fine grids and weld them to the solder strips. When using the laser opening + electroplating method, laser damage in this area is unacceptable, so as a trade-off, some researchers have chosen to use Ag paste for the main grids and electroplating for the fine grids, but this still requires the use of Ag paste, which limits the cost reduction.

[0088] The conventional method of electroplating the electrodes of solar cells is as shown in Figure 7, where the cathode fixture needs to clamp the solar cell (the press needle contacts the specially designed open membrane area), and then the cell is immersed in a plating bath with a Ni seed layer, and after Ni plating, it is placed in a cleaning bath, then in a water bath for cleaning, and after cleaning, it is placed in a Cu plating bath for Cu plating, then in a water bath for cleaning, and then in a Sn plating bath for Sn plating. In order to ensure the stability of the clamping and the relatively small stress, the area of ​​the electrode piezoelectric treatment needs to be large enough, which will lead to localized laser damage losses and affect the appearance of the product.

[0089] The poor electrical conductivity of the silicon wafer substrate causes non-uniformity in the surface potential, which affects the uniformity of the electroplating within the battery sheet, and in order to compensate for this shortcoming, it is usually necessary to provide multiple electrode press needles on a single battery sheet, which further exacerbates the above-mentioned effects. Because different areas of a single battery sheet and the plating baths in which different batteries are located do not match, there are also differences in the concentrations of chemical components on its surface, which causes differences in the thickness of the electroplating within and between sheets of the product.

[0090] In addition, due to limitations imposed by the machine structure, the number of battery sheets that can be clamped in a single plating tank is limited, limiting its production capacity and making it difficult to support large-scale production.

[0091] In the present disclosure, the implementation for electroplating the electrode is as shown in Figure 8, in which a single seed layer 2 is grown on the back side of the battery sheet, and the growth manner of the seed layer 2 is preferably by physical vapor deposition technology. This seed layer 2 may be partially removed after electroplating or may be partially removed before electroplating, but at least during electroplating, the coverage area of ​​the seed layer 2 still accounts for >20% of the total area.

[0092] At this time, the seed layer 2 is located on the top surface of the back surface of the battery so that the seed layer 2 can be in good contact with the cathode electrode completely. Then, the battery sheet is horizontally conveyed by chains in the electroplating tank, and the rollers rotate to move the battery sheet, and the roller on one side is the cathode of the electroplating system made of conductive material. The battery achieves electroplating by continuously or almost continuously contacting the cathode roller during horizontal conveyance.

[0093] The above-mentioned method for electroplating electrodes has the following advantages: 1) by designing a tank body with an appropriate length and improving the conveying speed, an ideal sheet production volume per unit time can be achieved and the needs of large-scale mass production can be met; 2) the conductivity of the seed layer is high, and at the same time, the surface of the battery sheet is uniformly in contact with the chemical solution, thereby improving the uniformity and stability of the electroplating process; and 3) the laser opening area is independent of the electrode width, and the main grid area and the cathode contact area do not require additional laser opening, which effectively reduces laser loss.

[0094] From the above introduction, those skilled in the art can clearly recognize that the main beneficial effect of the present disclosure is the organic combination of both large-area growth of seed layer and horizontal electroplating. When using the conventional seed layer 2 electroplating technology, horizontal electroplating cannot be applied to the production of solar cells because it cannot form good contact with the cathode roller; when using the conventional vertical electroplating technology in the process based on large-area seed layer 2, it is difficult to realize the large-scale popularization of electroplating technology due to problems such as stability, uniformity, and production capacity that are somewhat too low.

[0095] Furthermore, if the passivation contact technology is used in the area under the electrode of the battery, that is, if the tunnel oxide layer + polysilicon passivation layer is grown, a more ideal effect can be obtained. The reason is that 1) the seed layer grown by physical vapor deposition (especially sputtering) is likely to cause a certain impact damage to the surface, and the passivation contact structure on the substrate surface can effectively prevent the impact damage, and 2) the passivation contact structure can effectively reduce the laser opening damage. Therefore, the passivation contact structure and the physical vapor deposition seed layer + horizontal electroplating technology are an organic combination, which effectively solves the adverse effects caused by the physical vapor deposition seed layer + horizontal electroplating technology.

[0096] In describing the present disclosure, orientations or positional relationships indicated by terms such as "center," "lateral," "upper," "lower," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer" are orientations or positional relationships shown in the drawings, and are used merely to facilitate or simplify the description of the present disclosure, and are not intended to represent or imply that the devices or parts shown necessarily have a specific orientation or a specific oriented structure and operation, and therefore should not be construed as limiting the present disclosure.

[0097] Additionally, the terms "first" and "second" are used for descriptive purposes only and should not be understood to indicate or imply a relative importance or to imply a number of the technical features depicted. Thus, a feature qualified as "first" or "second" may explicitly or implicitly include one or more of said features. In the description of this disclosure, unless otherwise specified, "plurality" means two or more. Additionally, the term "comprises" and any variations thereof are intended to cover a non-exclusive inclusion.

[0098] Although the present disclosure has been described according to the embodiments, the present device may be modified and improved without departing from the principles of the present invention, and any technical means obtained by equivalent replacement or equivalent transformation or the like is within the scope of protection of the present disclosure.

Claims

1. An electrode structure for a solar cell including a conductive layer, the conductive layer having an end connected to the solar cell, the seed layer being provided at the end, the width of the seed layer being smaller than the width of the conductive layer, a predetermined surface of the conductive layer and a surface of the solar cell forming a suspension structure, the predetermined surface being a surface of the conductive layer adjacent to the seed layer and not covered by the seed layer; Electrode structure of a solar cell.

2. The seed layer is made of an alloy material, and the components of the seed layer include a functional component and a strengthening component, and the functional component and the strengthening component are mixed in a certain ratio. The electrode structure of a solar cell according to claim 1 .

3. The functional component is a metal having a wavelength range of 850 nm to 1200 nm and an average refractive index of less than 2; The electrode structure of a solar cell according to claim 2 .

4. The functional component is one or more of Al, Ag, Cu, and Mg, and the reinforcing component includes one or more of Mo, Ni, Ti, W, Cr, Si, Mn, Pd, Bi, Nb, Ta, Pa, and V, and the content ratio of the functional component is >50%, the content ratio of the functional component is the ratio of the content of the functional component to the total content, and the total content is the sum of the content of the functional component and the content of the reinforcing component. The electrode structure of a solar cell according to claim 3 .

5. The seed layer is produced by one of the following methods: physical vapor deposition, screen printing, chemical vapor deposition, electroplating or chemical plating; The electrode structure of a solar cell according to claim 2 .

6. The conductive layer is made of a conductive metal, and the material of the conductive layer includes one or more of Cu, Ag, and Al; The electrode structure of a solar cell according to claim 1 .

7. The conductive layer is produced by one of the following methods: physical vapor deposition, screen printing, chemical vapor deposition, electroplating or chemical plating; The electrode structure of a solar cell according to claim 6.

8. The electrode structure further includes a protective layer provided on a surface of the conductive layer away from the seed layer, the protective layer being made of Sn or Ag, and the protective layer is manufactured by one of the following methods: physical vapor deposition, screen printing, chemical vapor deposition, electroplating, or chemical plating. The electrode structure of a solar cell according to claim 1 .

9. the suspension structure has a suspension mean height range of 10 nm to 50 μm, the suspension mean height being the distance between the predetermined surface and the surface of the solar cell; The electrode structure of a solar cell according to any one of claims 1 to 8.

10. a layer of dielectric film is further provided on a surface of the solar cell, an opening is formed in the dielectric film to expose a portion of the surface of the solar cell, and the seed layer is locally in contact with the solar cell through the opening; The electrode structure of a solar cell according to claim 8.

11. a transparent conductive oxide thin film is further provided between the seed layer and the dielectric film, and a part of the transparent conductive oxide thin film is in contact with the solar cell through the opening provided in the dielectric film; The electrode structure of a solar cell according to claim 10.

12. The width of the seed layer = (20% to 98%) * the width of the conductive layer; The electrode structure of a solar cell according to claim 1 .

13. the width of the conductive layer minus the width of the seed layer > 5 μm; The electrode structure of a solar cell according to claim 1 .

14. The width of the seed layer=(30% to 90%)*the width of the conductive layer; The electrode structure of a solar cell according to claim 1 .

15. the width of the conductive layer minus the width of the seed layer > 10 μm; The electrode structure of a solar cell according to claim 14.

16. The seed layer is formed by stacking a plurality of sub-seed layers. The electrode structure of a solar cell according to claim 1 .

17. the content of the functional component in the stacked subseed layers gradually decreases along a direction away from the solar cell; The electrode structure of a solar cell according to claim 16.

18. The seed layer has a thickness of 10 nm to 1000 nm. The electrode structure of a solar cell according to claim 1 .

19. The conductive layer has a thickness of 1 to 800 μm. The electrode structure of a solar cell according to claim 11.

20. The electrode structure according to any one of claims 1 to 19, Solar cell.

21. The solar cell according to claim 20, Solar cell module.

22. The solar cell module according to claim 21, Photovoltaic power generation system.

23. forming a patterned mask layer over the solar cell; forming a pre-seed layer on a surface of the solar cell adjacent to the mask layer; forming a conductive layer on a surface of the pre-seed layer remote from the solar cell; removing the preliminary seed layer that is not in contact with the substrate using the mask layer as a mask to obtain a seed layer, and removing the patterned mask layer. A method for manufacturing an electrode structure.